Between Virtue and Virtuality - Ward, Graham (Theology today, 2002)
This essay performs a cultural negotiation between Christian theological discourse and the discourses of the Internet. It argues that Christian theology can neither ignore what is taking place globally and affecting all our lives in one way or another, nor pretend that this advanced technology is simply another tool that can be used or not used as occasion demands. Theology must engage Internet culture as this new culture transfigures social life. This means recognizing that theology, too, will be transfigured as the conditions of social living are transfigured. Being proactive, the work of theology will be affected by the engagement itself. But through this engagement, Christian theology will understand the distinctive contribution it can make to a critical and reflexive analysis of digital living. For there is a need for the engagement with Internet culture to be critical. There are moral and metaphysical questions posed by cyberpower. There are theological questions to be asked about its electronic dreams and sublime desires.